Determinants of health care use among homeless individuals: evidence from the Hamburg survey of homeless individuals - André Hajek; Franziska Bertram; Fabian Heinrich; Victoria van Rüth; Benjamin Ondruschka; Benedikt Kretzler; Christine Schüler; Klaus Püschel; Hans-Helmut König (BMC, 2021)
Abstract Background To identify the determinants of health care use among homeless individuals. Methods Data were taken from the Hamburg survey of homeless individuals (n = 100 individuals in the here used model, mean age 44.8 years, SD 12.5) focusing on homeless individuals in Hamburg, Germany. The number of physician visits in the past 3 months and hospitalization in the preceding 12 months were used as outcome measures. Drawing on the Andersen model of health care use as a conceptual framework, predisposing characteristics, enabling resources and need factors as well as psychosocial variables were included as correlates. Results Negative binomial regressions showed that increased physician visits were associated with being female (IRR: 4.02 [95% CI: 1.60-10.11]), absence of chronic alcohol consume (IRR: 0.26 [95% CI: 0.12-0.57]) and lower health-related quality of life (IRR: 0.97 [95% CI: 0.96-0.98]). Furthermore, logistic regressions showed that the likelihood of hospitalization was positively associated with lower age (OR: 0.93 [95% CI: 0.89-0.98]), having health insurance (OR: 8.11 [2.11-30.80]) and lower health-related quality of life (OR: 0.97 [95% CI: 0.94-0.99]). Conclusions Our study showed that predisposing characteristics (both age and sex), enabling resources (i.e., health insurance) and need factors in terms of health-related quality of life are main drivers of health care use among homeless individuals. This knowledge may assist in managing health care use.